On the extraction of aromatic compounds from hydrocarbons by imidazolium ionic liquids - Cassol, Cláudia Cristiana (2007)
The liquid-liquid equilibrium for the ternary system formed by n-octane and aromatic (alkylbenzenes) and heteroaromatic compounds (nitrogen and sulfur containing heterocyles) and 1-alkyl-3-methylimidazolium ionic liquids (ILs) associated with various anions has been investigated. The selectivity on the extraction of a specific aromatic compound is influenced by anion volume, hydrogen bond strength between the anion and the imidazolium cation and the length of the 1-methyl-3-alkylimidazolium alkyl side chain. The interaction of alkylbenzenes and sulfur heterocyles with the IL is preferentially through CH-π hydrogen bonds and the quantity of these aromatics in the IL phase decreases with the increase of the steric hindrance imposed by the substituents on the aromatic nucleus. In the case of nitrogen heterocycles the interaction occurs preferentially through N(heteroaromatic)-H(imidazolium) hydrogen bonds and the extraction process is largely controlled by the nitrogen heterocycle pKa. Competitive extraction experiments suggest that benzene, pyridine and dibenzothiophene do not compete for the same hydrogen bond sites of the IL.